T cells expanded from renal cell carcinoma display tumor-specific CD137 expression but lack significant IFN-γ, TNF-α or IL-2 production. (1st January 2021) - van Asten, Saskia D.; de Groot, Rosa; van Loenen, Marleen M.; Castenmiller, Suzanne M.; de Jong, Jeroen; Monkhorst, Kim; Haanen, John B.A.G.; Amsen, Derk; Bex, Axel; Spaapen, Robbert M.; Wolkers, Monika C.
ABSTRACT: Metastatic renal cell carcinoma (RCC) has a poor prognosis. Recent advances have shown beneficial responses to immune checkpoint inhibitors, such as anti-PD-1/PD-L1 antibodies. As only a subset of RCC patients respond, alternative strategies should be explored. Patients refractory to anti-PD-1 therapy may benefit from autologous tumor-infiltrating lymphocyte (TIL) therapy. Even though efficient TIL expansion was reported from RCC lesions, it is not well established how many RCC TIL products are tumor-reactive, how well they produce pro-inflammatory cytokines in response to autologous tumors, and whether their response correlates with the presence of specific immune cells in the tumor lesions. We here compared the immune infiltrate composition of RCC lesions with that of autologous kidney tissue of 18 RCC patients. Tcell infiltrates were increased in the tumor lesions, and CD8 + Tcell infiltrates were primarily of effector memory phenotype. Nine out of 16 (56%) tested TIL products we generated were tumor-reactive, as defined by CD137 upregulation after exposure to autologous tumor digest. Tumor reactivity was found in particular in TIL products originating from tumors with ahigh percentage of infiltrated Tcells compared to autologous kidney, and increased CD25 expression on CD8 + Tcells. Importantly, although TIL products had the capacity to produce the key effector cytokines IFN-γ, TNF-α or IL-2, they failed to produce significant amounts in response to autologous tumor digests. In conclusion, TIL products from RCC lesions contain tumor-reactive Tcells. Their restricted tumor-specific cytokine production requires further investigation of immunosuppressive factors in RCC and subsequent optimization of RCC-derived TIL culture conditions.